Analysis of the Employee Performance of the Palopo State Islamic Institute in Achieving Institutional Achievements - Suharsih Suharsih; Ulfa Ulfa (Jurnal Public Policy, 2022)
This study aims to analyze the performance of employees in the financial sub-sector of the Palopo State Islamic Institute. The research method used in this study is qualitative, using a post-positivist research paradigm, which uses theory as a guide and a central point in finding and exploring what is hidden from the various phenomena studied by using data collection techniques, namely observation, in-depth interviews, and documentation. The results show that the performance of IAIN Palopo finance employees in achieving institutional performance with performance indicators from Russell, namely ability, motivation, and opportunity, can be said to be not optimal because the opportunity/opportunity indicators are not following government regulation no. 11 of 2017 concerning the management of Civil Servants. So it is expected that the culture of giving rewards/appreciation for employees with good performance and punishment for low-performing employees.